Growth of meromorphic solutions of higher-order linear differential equations - Wenjuan Chen; Junfeng Xu (Electronic Journal of Qualitative Theory of Differential Equations, 2009)
In this paper, we investigate the higher-order linear differential equations with meromorphic coefficients. We improve and extend a result of M.S. Liu and C.L. Yuan, by using the estimates for the logarithmic derivative of a transcendental meromorphic function due to Gundersen, and the extended Winman-Valiron theory which proved by J. Wang and H.X. Yi. In addition, we also consider the nonhomogeneous linear differential equations.